Seloc Honda outboards 1978-01 repair manual : 2-130 horsepower, 1-4 cyclinder - Maher, Kevin M. G. (Seloc Publications, 2004)
SELOC Marine maintenance and repair manuals offer the most comprehensive, authoritative information available for outboard, inboard, stern-drive and diesel engines, as well as personal watercraft. SELOC has been the leading source of how-to information for the marine industry since 1974. Designed and written to serve the needs of the professional mechanic, do-it-yourself boat enthusiast, instructor and student, these manuals are based on actual teardowns done by Chilton Marine's editors/authors in our on-site facility. Providing complete coverage on everything from basic maintenance to engine overhaul, every manual features: Simple-to-follow, step-by-step, illustrated procedures Hundreds of exploded drawings, photographs and tables Troubleshooting sections, accurate specifications and wiring diagrams Recognized and used by technical trade schools as well as the U.S. military Covers all 2-130 Hp, 1 to 4-cylinder models.